Approximating the metric 2-Peripatetic Salesman Problem - Della Croce, Federico; Paschos, Vangelis; Calvo, Roberto (Algorithmic Operations Research)

(untitled) (Preeminent Academic Facets Inc., 2009)
This paper deals with the 2-Peripatetic Salesman Problem for the case where costs respect the triangle inequality. The aim is to determine 2 edge disjoint Hamiltonian cycles of minimum total cost on a graph. We first present a straightforward 9/4 approximation algorithm based on the well known Christofides algorithm for the travelling salesman problem. Then we propose a 2(n−1)/n-approximation polynomial time algorithm based on the solution of the minimum cost two-edge-disjoint spanning trees problem. Finally, we show that by partially combining these two algorithms, a 15/8 approximation ratio can be reached if a 5/4 approximation algorithm can be found for the related problem of finding two edge disjoint subgraphs consisting of a spanning tree and a Hamiltonian cycle of minimum total cost.